Correlation Analysis between Wheat Flour Solvent Retention Capacity and Gluten Aggregation Characteristics - Wei Gong; Xiaohua Wang; Fengjiao Wang; Jinshui Wang (Foods, 2023)
Solvent retention capacity (SRC) is a test for the solvation of wheat flour. Its functional contribution was predicted according to the swelling behavior of different diagnostic solvents to different polymeric components of wheat. Ten commercial wheat flour varieties were used as raw materials in this study. The flour quality, gluten aggregation and solvent retention capacity, and their correlations were analyzed. The results showed that protein content, wet gluten content, dry gluten content and the swelling index of glutenin were positively correlated with torque maximum (BEM), torque 15 s before maximum torque (AM), torque 15 s after maximum torque (PM) and gluten aggregation energy (AGGEN). Moreover, they were significantly correlated with the solvent retention capacity. BEM, AM, PM and AGGEN were positively correlated with standard solvent water-SRC (WSRC) and lactic acid-SRC (LASRC). For supplemental solvents, ethanol-SRC (EthSRC) was positively correlated with AGGEN. Sodium dodecyl sulphate-SRC (SDSSRC) was highly correlated with peak maximum time (PMT). Metabisulfite-SRC (MBSSRC) and MBS + SDSSRC were also significantly correlated with BEM, AM, PM and AGGEN sodium metabisulfite. There were significant correlations between gluten aggregation characteristic, standard SRC solvent and supplemental solvent. This study provides a theoretical basis for the evaluation of wheat flour quality.